Oxidative stress and hepatotoxicity in rats induced by poisonous pufferfish (Lagocephalus lagocephalus) meat - M Saoudi; A Abdelmouleh; F Ellouze; K Jamoussi; A El Feki (Journal of Venomous Animals and Toxins including Tropical Diseases, 2009)
This study was undertaken to evaluate the effect of pufferfish (Lagocephalus lagocephalus) meat poisoning on hepatic functions of Wistar rats. For this purpose, groups of rats (Lcr, Lcu+b and Lcu-b) received diet supplemented with 10% of raw or cooked meat, respectively, with or without cooking water of L. lagocephalus while groups Mcr and Mcu+b received diet supplemented with 10% of raw or cooked meat of Liza aurata, which were used as a negative control. In Lcu+b group, ALT, AST and ALP rates (hepatic enzyme markers) decreased after two months of treatment, indicating liver damage. We also observed an increase of 54 and 65% of thiobarbituric acid reactive substances (TBARS) in their livers respectively 48 hours and two months after treatment compared to controls. The catalase (CAT) activity in group Lcu+b decreased (p < 0.05) after two periods of treatment, whereas metallothionein (MT) level significantly increased and decreased, respectively after 48 hours and two months. In fact, in the histological analysis of the livers from Lcu+b treated group, we observed an increase in vacuolisation, necrosis, hepatocytes ballooning and sinusoids dilation. These results indicate that L. lagocephalus meat cooked with water produces hepatotoxicity and oxidative damage.